Concurrent coronary artery disease and immune thrombocytopenia: a systematic review - Rahhal, Alaa; Provan, Drew; Shunnar, Khaled; Najim, Mostafa; Ahmed, Ashraf Omer; Rozi, Waail; Al-Khabori, Murtadha; Marashi, Mahmoud; AlRasheed, Mona; Osman, Hani; Yassin, Mohamed (Frontiers in Medicine, 2023)
Introduction: Coronary Artery Disease (CAD) management in the setting of Immune Thrombocytopenia (ITP) remains very challenging to clinicians as a reasonable balance between bleeding and thrombosis risks needs to be achieved, and the evidence guiding such management is scarce.We conducted a systematic review following the PRISMA guidelines to summarize the available literature on the management and outcomes of CAD coexisting with ITP. We searched PubMed and Embase for studies published in English exploring CAD and ITP management till 05/10/2022. Two independent reviewers screened and assessed the articles for inclusion. Patients' characteristics, CAD treatment modalities, ITP treatment, and complications were reported.We identified 32 CAD cases; among which, 18 cases revascularized with Percutaneous Coronary Intervention (PCI), 12 cases underwent Coronary Artery Bypass Graft surgery (CABG), and two cases were managed conservatively. More than 50% were male, with a mean age of 61 ± 13 years with a mean baseline platelet count of 52 ± 59 x 10 9 /L. Irrespective of the revascularization modality, most patients were treated with either corticosteroids alone, intravenous immunoglobulins (IVIG) alone, or in combination. Among those who underwent PCI, two patients had bleeding events and one patient died. Similarly, among those with CABG, one patient developed bleeding and one patient died.We found that revascularization with either PCI or CABG with the concurrent use of corticosteroids and/or IVIG for ITP was feasible, with an existing non-negligible risk of bleeding and mortality.